(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, Filipinos, especially millennials and younger generations, are interested in different kinds of products that offer lower prices and good quality. Mr. D.I.Y is a retail chain that offers a comfortable and enjoyable family shopping experience. It has an average floor space of 10,000 square feet and offers ten categories of products with an average of 18,000 varieties in each store. Mr. D.I.Y focuses on improving customer retention by providing excellent service and satisfaction. However, some problems, such as inventory management, product placement, and lack of employee knowledge, have been identified, which could negatively impact customer satisfaction. Therefore, Mr. D.I.Y must synchronize inventory levels, maintain store cleanliness, train staff, and provide consistent quality and service to retain customers. The respondents were 18-24 years old, both male and female, employed. 2.1 The description of male and female groups of respondents assesses the customer level of satisfaction. “Very Strongly Agree” in terms of the Unique way of serving customers and the way welcoming the customer appreciated was presented to the customers. “Strongly Agree” Fast process of servicing and good communication of the employee to the customers. 3. The difference between the assessment of the 2 SOPs serving multiple customers “1st rank” 4. The hindrances experienced by the customers and the solution offered by the owner the highest rank from males in “Serving multiple customers” and “shortage of the product” 5. The customer retention program suggests offering incentives like discounts and exclusive access to events, personalized communication, customer surveys, branded gifts, and exclusive experiences. Moreover, MR.DIY recognizes the importance of sustainability and corporate social responsibility, implementing various initiatives to reduce waste, conserve energy, and support local communities. In conclusion, MR.DIY has emerged as a dominant player in the retail industry, providing affordable, diverse, and high-quality products to millions of customers. Its customer-centric approach, wide range of products, affordable pricing strategy, and technological innovation have positioned it for future growth, making it a brand to watch in Southeast Asia.